Beyond the lecture hall: fostering soft skills in Malaysian university students through a democratic classroom - Hamzah, Lina Mursyidah; Majid, Sheikha; Mohd Yusoff, Norhayati; Hussien, Suhailah (Penerbit UiTM, 2025)
This study aims to investigate how democratic classrooms can help to foster students' soft skills. The study employs a qualitative methodology, specifically adopting a case study technique. The researcher conducted semi-structured interviews with six Malaysian university students. The data were analysed through thematic analysis. The results indicate that a democratic classroom has the ability to enhance students' soft skills. Moreover, it can also improve students' critical thinking skills. This study suggests that instructors should ensure that the learning environment significantly influences students' soft skills. The findings of this study contribute towards the body of knowledge relating to the promotion of more democratic teaching and learning in the context of Malaysian higher education.